Sistem Pendukung Keputusan Optimasi Perencanaan Stok Obat Menggunakan Metode Weight Moving Average - Opitasari Opitasari; Yadarabullah Yadarabullah (Bulletin of Computer Science Research, 2026)
A common issue in pharmacy inventory management is the occurrence of stockouts or overstock, which affects patient service. This study aims to design a decision support system that optimizes drug stock planning accurately and efficiently using the Weighted Moving Average (WMA) method. The system is developed as a web-based application using the Laravel framework and MySQL database, utilizing hisorical sales data as the basis for forecasting drug demand. The evaluation results indicate that the WMA method provides excellent prediction accuracy, achieving a MAPE value of 8.63%. This system assists pharmacists in making data-driven decisions, minimizing stock risks, and supporting the digitalization of inventory management in pharmacies